The Elephant in the Family Room: Work–Family Considerations as Central to Evolving HR and I-O. Issue 1 (23rd March 2017) - Mills, Maura J.; Culbertson, Satoris S.
Abstract : In their focal article, Schiemann and Ulrich (2017 ) provide a broad overview of thoughts and insights by 73 of today's human resources/industrial–organizational (HR/I-O) leaders. It was both interesting and valuable to hear from those "in the trenches" every day and to learn what they considered to be the key recommendations, cautions, and needs central to the HR/I-O practice of today—and tomorrow. That said, we were surprised that, considering the zeitgeist of the current workscape, work–family considerations did not make more of an appearance in these reports of leaders' values and priorities for their organizations and for the field as a whole.